Changes in Maternal and Paternal Pain-Related Attitudes, Behaviors, and Perceptions across Pediatric Pain Rehabilitation Treatment: A Multilevel Modeling Approach. (16th June 2016) - Sieberg, Christine B.; Smith, Allison; White, Matthew; Manganella, Juliana; Sethna, Navil; Logan, Deirdre E.
Abstract : Objectives This prospective study compared paternal versus maternal factors and their impact on child outcomes in the context of an intensive pediatric pain rehabilitation program. Methods One hundred four youth with treatment refractory chronic pain and their parents enrolled in an intensive pediatric pain rehabilitation program completed measures of pain, functional disability, and parent pain-related attitudes, perceptions, and behaviors at admission and discharge. Results Linear mixed models were used. Controlling for significant demographic and clinical characteristics, mothers and fathers who were present for the program typically demonstrated significantly better improvement from admission to discharge compared with nonpresent fathers. Mothers made the most significant gains in protective parent responses. Children also had significant decreases in pain and improvements in functioning over time. Conclusions Results indicate the efficacy of this treatment model for both children with chronic pain and their parents and highlights the importance of parental presence in treatment.